2023
DOI: 10.1021/acssuschemeng.2c07337
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Deep Eutectic Solvent Reline in the Synthesis of Gold Nanoparticles

Abstract: This work presents a mechanistic understanding of the synthesis of small (<3 nm) gold nanoparticles in a nontoxic, eco-friendly, and biodegradable eutectic mixture of choline chloride and urea (reline) without the addition of external reducing or stabilization agents. Reline acts as a reducing agent by releasing ammonia (via urea hydrolysis), forming gold nanoparticles even at trace ammonia concentration levels. Reline also affects the speciation of the gold precursor forming gold chloro-complexes, stabilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…The initial degradation of the DES based on ChCl, starting at 85 °C, was already reported in the literature. Due to this fact, the TGA, NMR, and Karl Fischer analyses of fresh DES–ZnO were performed. First, the temperature at which the weight loss of DES–ZnO begins on the TGA/DTG thermal curve was determined (Chart SI.1 80 °C).…”
Section: Resultsmentioning
confidence: 90%
“…The initial degradation of the DES based on ChCl, starting at 85 °C, was already reported in the literature. Due to this fact, the TGA, NMR, and Karl Fischer analyses of fresh DES–ZnO were performed. First, the temperature at which the weight loss of DES–ZnO begins on the TGA/DTG thermal curve was determined (Chart SI.1 80 °C).…”
Section: Resultsmentioning
confidence: 90%
“…Unfortunately, the specific mechanism for tuning of the various morphologies is yet to be fully understood. Datta et al 107 systematically investigated the role of ChClurea DES on the formation of small (<3 nm) Au nanoparticles. They found that the ChCl-urea DES played multiple roles in the formation of Au nanoparticles.…”
Section: Nanomaterials Synthesismentioning
confidence: 99%
“…Datta et al 107 systematically investigated the role of ChCl–urea DES on the formation of small (<3 nm) Au nanoparticles. They found that the ChCl–urea DES played multiple roles in the formation of Au nanoparticles.…”
Section: As Solventsmentioning
confidence: 99%
“…As the field advances, a critical focus will be on understanding the fundamental mechanisms underlying materials synthesis within DESs. 26,27 These mechanisms enable researchers to not only harness the current capabilities more effectively but also to design novel DESs tailored specifically for unique materials synthesis challenges. The marriage of green chemistry principles, meticulous engineering, and innovative materials design is poised to reshape industries and technologies in ways that are sustainable, efficient, and at the forefront of scientific innovation.…”
Section: Introductionmentioning
confidence: 99%